PERBEDAAN KEBIJAKAN KANTOR BERSAMA SAMSAT I DAN KANTOR BERSAMA SAMSAT II KOTA SURABAYA DALAM MEMBERIKAN PELAYANAN - Subroto Subroto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The purpose of this research is to analyze the different policy applications of Integrated Under One Roof Administration System (Samsat) and its implementation which is related to the services  towards the society as the owners of vehicles in Surabaya. In order that purpose can be realized, the witer conducted a comparative research between the implementation of the integrated instruction (Samsat) in 1993 with that of  the integrated office (Samsat) in 1999 of Surabaya I and the integrated office of Surabaya II.The results of the field research show that the work performance of Samsat in Surabaya  is low. The lowest performance was in legalization of vehicle license, extention of motor vehicle license, and new vehicle and incoming mutation. The results also show that the work performance of Samsat I is lower than Samsat II.